COMPARATIVE ANALYSIS OF TECHNILOGIES OF CHITOSAN PRODUCTION FROM DEAD BEES - Abramova, Marina; Vasylchenko, Olga (Proceedings of National Aviation University (archive), 2017)
Objective: The aim of this work is to study the characteristics of technology of chitosan obtaining from unconventional sources, namely from dead bees. Methods: The article considers three methods of chitosan obtaining from dead bees, namely the technology with the usage of dead bees with low degree of drying; the technology with the usage of dead bees with high degree of drying; the technology with the usage of dead bees with high degree of drying but without separation of deproteination and deacetylation stages. Results: It is proved that the technology with the usage of dead bees with high degree of drying but without separation of deproteination and deacetylation stages does not require high temperatures and long time. Yield of chitosan with the use of this technology is 21-24%. Discussion: The expediency of dead bees usage as raw material for the production of chitosan in Ukraine is shown. The technologies of chitosan obtaining from dead bees are compared, the most efficient one is chosen, which provide the highest yield of the finished product, so it is the most promising for the application in practice.